The vampire Lestat - Rice, Anne, 1941-2021 (Rice, Anne, 1941-2021. Vampire chronicles, 2014)
"Lestat. The vampire hero of Anne Rice’s enthralling novel is a creature of the darkest and richest imagination. Once an aristocrat in the heady days of pre-revolutionary France, now a rock star in the demonic, shimmering 1980s, he rushes through the centuries in search of others like him, seeking answers to the mystery of his eternal, terrifying existence. His is a mesmerizing story—passionate, complex, and thrilling."--